FACTORS AFFECTING THE TRANSFER OF FUNCTION OF ORANGE LAND TO OIL PALM IN SUMBER BAKTI VILLAGE - Salsabila Rahmi Sinaga; Devi Agustia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to identify and describe the extent to which the influence of farmer age, citrus farming experience, number of dependents, citrus capital, and total area of ​​citrus land on the conversion of citrus land to oil palm in Sumber Bakti Village, Darul Makmur District, Nagan Raya Regency. This study took 31 samples from a total of 31 populations with consideration of farmers converting citrus land to oil palm. Data collection techniques used in this study were observation and interviews. Data analysis techniques using descriptive analysis, quantitative analysis using multiple linear regression analysis. The results of the study simultaneously show that the variables of farmer's age, citrus farming experience, number of dependents, citrus capital, and the total area of ​​citrus land influences the farmer's decision to change land functions. Although partially only the variables of farmer's age, citrus capital, and total area of ​​citrus land that influence farmers' decisions to convert citrus land to oil palm.